Cardioprotective role of zofenopril in hypertensive patients with acute myocardial infarction: a pooled individual data analysis of the SMILE studies. (4th July 2017) - Borghi, Claudio; Omboni, Stefano; Reggiardo, Giorgio; Bacchelli, Stefano; Degli Esposti, Daniela; Ambrosioni, Ettore
Abstract: Purpose: The four SMILE studies demonstrated that early administration of zofenopril following acute myocardial infarction is prognostically beneficial compared to placebo or other angiotensin-converting enzyme (ACE) inhibitors. In the present retrospective pooled analysis of individual SMILE studies, we evaluated the efficacy of zofenopril on cardiovascular (CV) outcomes in 1880 hypertensive and 1662 normotensive patients. Materials and methods: Four hundred and forty-nine hypertensives and 486 normotensives were treated with placebo, 980 and 786 with zofenopril 30–60 mg daily, 252 and 259 with lisinopril 5–10 mg daily, 199 and 131 with ramipril 10 mg daily, for 6 to 48 weeks. Results: The 1-year risk of death or hospitalization for CV causes was significantly reduced with zofenopril and lisinopril vs. placebo in both hypertensive (HR: 0.65; 95%CI: 0.48–0.86; p = .003 and .60, .36–.99; p = .049, respectively) and normotensive patients (0.56, 0.42–0.75; p = .0001 and .51, .28–.90; p = .020), whereas this was not the case for ramipril (hypertensives: 1.02, 0.69–1.52; p = .918; normotensives: 0.91, 0.59–1.41; p = .670). Zofenopril significantly reduced the risk of CV outcomes vs. the other two ACE-inhibitors pooled together in hypertensive (0.76; 0.58–0.99; p = .045), but not in normotensive patients (0.77; 0.55–1.10; p = .150). Conclusions: In cardiac patients of the SMILE studies with arterial hypertension treatment with the ACE-inhibitor zofenopril was beneficial in reducing the 1-year risk of CV events as compared to placebo and ramipril. An efficacy similar to that of zofenopril was observed with lisinopril.